Factors influencing university vote: analysis of information for elections at a public university in southeast Mexico - Solano González, Rodrigo; Cuevas Gómez, Martha Elena (Acta Universitaria, 2026)
As a starting point, this research considered the information available to university students in the 2024 presidential elections, aiming to determine young voters’ knowledge of the presidential campaigns and the three candidates’ policy proposals. A documentary review was done and a mixed-method approach was adopted through a survey applied to 176 university students from 12 faculties in the state of Tabasco. Results revealed a lack of i digital interaction on social media by the presidential candidates and a marked tendency toward economic factors as the fundamental reason for voting. Situations such as organized crime and deficiencies in the health sector are recognized as among the main problems facing the country.